Financial Distress: Real Interest Rate, Operating Cash Flow, Operating Capacity, Sales Growth dan Kepemilikan Institusional - Anistya Dhifa Pratitasari; Kusumawati, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Financial distress is a condition of continuous financial decline in a company caused by incorrect decision-making, management weaknesses, lack of cash flow and inability to pay obligations, which is one indicator of bankruptcy. This study analyzes the effect of real interest rate, operating cash flow, operating capacity, sales growth and institutional ownership on financial distress in primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used in this study was purposive sampling. A total of 123 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results of the study provide empirical evidence that real interest rate, operating cash flow, operating capacity, and institutional ownership have a significant effect on financial distress. Meanwhile, sales growth has no effect on financial distress. These findings provide insight for companies, investors, and regulators in understanding the factors that influence financial distress to maintain the company and be able to compete with competitors.